2018
DOI: 10.1292/jvms.17-0036
|View full text |Cite
|
Sign up to set email alerts
|

Systemic cytokine response in pigs infected orally with a <i>Lawsonia intracellularis</i> isolate of South Korean origin

Abstract: In the swine industry, Lawsonia intracellularis is one of the main enteric pathogens; it causes acute intestinal hemorrhage (proliferative hemorrhagic enteropathy) in naïve adult pigs and a wasting disease (proliferative enteropathy) in growing pigs. Among many kinds of cytokines, interferon-γ (IFN-γ) has previously been reported to play a significant role in limiting intracellular infection and increasing cellular proliferation associated with L. intracellularis. However, the levels of various circulating inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…A recent study reported that IL-6, as a pro-inflammatory cytokine, could induce intestinal epithelial barrier dysfunction and play a role in the pathological process of inflammatory bowel disease (IBD) [53]. Intriguingly, Lawsonia was previously found to be significantly associated with the increase of IL-6 [54,55]; thus, a potential link between Lawsonia and IL-6 expression is further suggested by our current findings, although the mechanism behind this association remains to be established. Besides, in a mice model of acute pancreatitis, low-methoxyl PEC was found to downregulate TNF-α, IL-1β and IL-6 mRNA levels in ileal and colonic tissue, leading to the recovery of acute pancreatitis-associated disorder of the intestinal barrier [56].…”
Section: Discussionsupporting
confidence: 54%
“…A recent study reported that IL-6, as a pro-inflammatory cytokine, could induce intestinal epithelial barrier dysfunction and play a role in the pathological process of inflammatory bowel disease (IBD) [53]. Intriguingly, Lawsonia was previously found to be significantly associated with the increase of IL-6 [54,55]; thus, a potential link between Lawsonia and IL-6 expression is further suggested by our current findings, although the mechanism behind this association remains to be established. Besides, in a mice model of acute pancreatitis, low-methoxyl PEC was found to downregulate TNF-α, IL-1β and IL-6 mRNA levels in ileal and colonic tissue, leading to the recovery of acute pancreatitis-associated disorder of the intestinal barrier [56].…”
Section: Discussionsupporting
confidence: 54%
“…However, type 1 cytokine levels are often altered; for example, increased levels of interferon-gamma (IFN-γ), IL-6, IL-10, transforming growth factor–beta (TGF-β), and tumor necrosis factor–alpha (TNF-α) have been reported. 82 , 112 Insights into the L. intracellularis –specific IFN-γ–producing cell responses have been published using the enzyme-linked immunospot (ELISpot) assay for IFN-γ detection, as well as the use of IFN-γ receptor knockout mice. 28 , 30 , 83 , 91 , 95 , 112 These studies have concluded that IFN-γ is elevated in infected pigs from 10 dpi, peaking at 20 dpi, earlier than other cytokines ( Fig.…”
Section: Immunologymentioning
confidence: 99%
“…These results verified the decease increasing in domestic pig farms, especially during the period of fattening, which caused significant economic losses (Ayshpur et al, 2019). Ileitis diagnosis is based on clinical and epizootiological analysis, microscopic, serological methods, immunofluorescence method (IFA) and immunoperoxidase monolayer assay (IPMA) for the detection of the antibodies of Lawsonia intracellularis, detection of pathogen DNA by polymerase chain reaction, immunohistochemical analysis (IHC) and histopathological analysis (Bonaet al, 2003;Hardge et al, 2006;Ayshpur et al, 2019;Resendeet al, 2019;Visscheret al, 2018;Guedeset al, 2017;Pérez Gaudioet al, 2018;Yeh& Ga, 2018).…”
Section: Introductionmentioning
confidence: 99%